A case of multiple congenital anomalies including agenesis of the anterior cruciate ligament - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2008)
Congenital absence of the anterior cruciate ligament (ACL) is a very rare anomaly. It is usually diagnosed during arthroscopic intervention. We presented a 15-year old male patient whose diagnosis was based on findings of physical examination and magnetic resonance imaging. Congenital absence of the ACL was associated with femoral shortening, dysplasia of the tibial intercondylar eminence, valgus knee, and compensatory scoliosis. Since the patient had no instability symptoms, and due to the presence of a negative pivot-shift test and multiple congenital anomalies, surgical treatment was not considered.
Keywords: Anterior cruciate ligament/abnormalities/radiography; femur; knee joint; ABSENCE; KNEE; RECONSTRUCTION; APLASIA